Complicating American Manhood: Marge Piercy’s Woman on the Edge of Time and the Feminist Utopia as a Site for Transforming Masculinities - Michael Pitts (European Journal of American Studies)
Contemporary feminist utopias make up an overlooked site for mining new masculinities amidst the current so-called crisis of masculinity in American culture. What is often overlooked in analyses of feminist texts and more specifically feminist utopian fiction is how the alteration of femininity necessitates the transformation of masculine ideals. Such novels, while varying in their focus, are united by an interest in transforming patriarchal masculinities and replacing them with an alternative informed by second wave and intersectional feminism. Through an analysis of masculinities in one such utopia, Marge Piercy’s Woman on the Edge of Time (1976), this essay traces how contemporary female speculative writers envision and propose new masculinities that, in opposition to their patriarchal counterparts, reject hierarchical perspectives and instead value equality, fraternity, and freedom.